A randomized controlled trial of an mHealth intervention for increasing access to HIV testing and care among young cisgender men and transgender women: the mLab App study protocol - Olivia R. Wood; Robert Garofalo; Lisa M. Kuhns; Thomas F. Scherr; Ana Paola Mata Zetina; Rafael Garibay Rodriguez; Nathanael Nash; Marbella Cervantes; Rebecca Schnall (BMC, 2021)
Abstract Background The number of youth living with HIV in the United States (US) continues to rise, and racial, ethnic, and sexual minority youth including young men who have sex with men (YMSM) and young transgender women (YTGW) bear a disproportionate burden of the HIV epidemic. Due to social and healthcare system factors, many YMSM and YTGW do not seek HIV testing services and are therefore less likely to be aware that they are infected. Mobile health technology (mHealth) has the ability to increase uptake of HIV testing among these populations. Thus, the mLab App-which combines HIV prevention information with a mobile phone imaging feature for interpreting at-home HIV test results-was developed to improve testing rates and linkage to care among Black, Latino, and other YMSM and YTGW living in New York City and Chicago and their surrounding areas. Methods This study is a three-arm randomized controlled trial among YMSM and YTGW aged 18-29 years. Participants are randomized to either the mLab App intervention including HIV home test kits and standard of preventive care, standard of preventive care only, or HIV home test kits and standard of preventive care only. Discussion mHealth technology used for HIV prevention is capable of delivering interventions in real-time, which creates an opportunity to remotely reach users across the country to strengthen their HIV care continuum engagement and treatment outcomes. Specifically during the COVID-19 pandemic, mHealth technology combined with at-home testing may prove to be essential in increasing HIV testing rates, especially among populations at high-risk or without regular access to HIV testing. Trial registration This trial was registered with Clinicaltrials.gov ( NCT03803683 ) on January 14, 2019.